Axially loaded stainless steel columns in case of fire - Lopes, Nuno
The simple model of Eurocode 3, for the fire resistance evaluation of stainless steel members, are based on the procedures used for carbon steel structural elements. However, due to the existing differences in the constitutive laws of these two materials, it is expected that it would not be possible to use, in both materials, the same formulae for the member stability calculation, as proposed in Eurocode 3. This paper aims at increasing the knowledge on the behaviour of stainless steel axially loaded columns at elevated temperatures. For this purpose, a geometrical and material non linear computer code has been used to determine the buckling load of these elements. The Eurocode formulae are evaluated and a new proposal, that ensures accurate and conservative results when compared with the numerical simulations, is presented.